2012
DOI: 10.1682/jrrd.2010.10.0201
|View full text |Cite
|
Sign up to set email alerts
|

Human distal sciatic nerve fascicular anatomy: Implications for ankle control using nerve-cuff electrodes

Abstract: Abstract-The design of neural prostheses to restore standing balance, prevent foot drop, or provide active propulsion during ambulation requires detailed knowledge of the distal sciatic nerve anatomy. Three complete sciatic nerves and branches were dissected from the piriformis to each muscle entry point to characterize the branching patterns and diameters. Fascicle maps were created from serial sections of each distal terminus below the knee through the anastomosis of the tibial and common fibular nerves abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 26 publications
4
42
0
Order By: Relevance
“…Although Sunderland [63] suggested that nerves were typically plexiform in nature, with axons traversing from fascicle to fascicle, there is sufficient evidence to suggest that, at least at the target locations along these nerves, the axons and fascicles within the nerve are more organized. While histological studies of the tibial and common peroneal nerve did not resolve to the axon level, they do not support the plexiform model within these nerves [47]. They do, however, suggest that there can be a large amount of variation in the location and number of fascicles between nerves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Sunderland [63] suggested that nerves were typically plexiform in nature, with axons traversing from fascicle to fascicle, there is sufficient evidence to suggest that, at least at the target locations along these nerves, the axons and fascicles within the nerve are more organized. While histological studies of the tibial and common peroneal nerve did not resolve to the axon level, they do not support the plexiform model within these nerves [47]. They do, however, suggest that there can be a large amount of variation in the location and number of fascicles between nerves.…”
Section: Discussionmentioning
confidence: 99%
“…While control of some ankle function has been noted in humans with stimulation via nerve cuff electrodes located as proximal as the spinal nerve roots, the selectivity of such systems was insufficient for control of standing balance and walking [46]. The fascicular anatomy of the human distal sciatic nerve and its main branches have been mapped to aid in the design of nerve cuff electrodes [47]. Computer models suggests that a FINE on the sciatic nerve will require many contacts for selective restoration of active ankle plantarflexion or dorsiflexion with balanced inversion and eversion [48].…”
Section: Introductionmentioning
confidence: 99%
“…41 The anatomy of the sciatic nerve has been well described in the literature. 1,13,14,20,33 The sciatic nerve originates from the anterior divisions of L-4 through S-3 and the posterior divisions of L-4 through S-2, thus forming the tibial and peroneal branches, respectively. 20 The sciatic nerve begins as these fibers coalesce entering the gluteal region through the greater sciatic foramen below the piriformis muscle 33 and then courses inferiorly at the midway point between the ischial tuberosity and greater trochanter of the femur.…”
Section: Discussionmentioning
confidence: 99%
“…The internal topography of the common peroneal nerve has been described. 2,21 The fascicles of the articular branch run with the fascicles of the deep peroneal nerve in the anterolateral portion of the common peroneal nerve at the level of the fibular head. This is the place to look on MRI.…”
Section: Clues To the Presence Of An Intraneural Cystmentioning
confidence: 99%